Assessment of cerebral dopamine D 2/3 formula-receptors in patients with bilateral vestibular failure - Jansen, Nathalie L.; Feuerecker, Regina; Becker-Bense, Sandra; Zwergal, Andreas; Wulff, Melanie; Xiong, Guoming; Wängler, Björn; Cumming, Paul; Bartenstein, Peter; Dieterich, Marianne; La Fougere, Christian (Journal of Vestibular Research-Equilibrium & Orientation, 2014)
Absence of peripheral vestibular input in bilateral vestibular failure (BVF) has been suggested to induce plastic reorganization in various brain regions. Among several neurotransmitters, dopamine is known to play a key role in cortico-striatal-sensorimotor processing. However, the role of dopamine in vestibular plasticity is scantly documented.Assessment of D 2/3 formula-receptors in patients with BVF.D 2/3 formula-receptor-PET using [18F]fallypride and MRI examinations were performed in 12 BVF-patients and 13 healthy controls.BVF-patients showed reduced D 2/3 formula-receptor availability (approximately 40%) in the temporo-parieto-occipital cortex bilaterally, including the multisensory vestibular cortex and visual motion-sensitive areas (MT/MST), as well as in the striatum and the right thalamus. Longer illness duration was associated with bilaterally lower D 2/3 formula-receptor availability in the middle/superior temporal gyrus (GTm/s). D 2/3 formula-receptor availability in the right GTm/s and bilateral insula decreased with severity of symptoms. BVF-patients with oscillopsia showed reduced D 2/3 formula-receptor availability in the right MT/MST and midbrain tectum.Reduced D 2/3 formula-receptor availability in multisensory vestibular cortical network areas and basal ganglia may indicate a receptor down-regulation due to the lack of peripheral vestibular input. The more pronounced decline in D 2/3 formula-receptor availability in the multisensory vestibular cortex in patients with prolonged illness suggests the occurrence of progressive changes in dopamine transmission.
EVALuna2:13849